One night, white lies - Lemmon, Jessica (Lemmon, Jessica. Bachelor pact., 2019)
Reid Singleton just had the best sex ever. When the brown-eyed bombshell turns out to be Drew Fleming<U+2014>his best friend<U+2019>s sister all grown-up<U+2014>Reid can<U+2019>t decide if he<U+2019>s furious at her ruse or ready for round two! Drew is determined to tame this stubborn bachelor. But she isn<U+2019>t the only person from Reid<U+2019>s past who will change his future<U+2026>